Librarian Performance in Circulation Services: An Examination of Management Practices and Challenges of the Manual System at the Pariaman City Library and Archives Service - Raisa Alya Fathonah; Nurizzati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Libraries play a critical role in supporting education, research, and community literacy; however, the effectiveness of their services depends substantially on librarian performance and circulation management. At the Pariaman City Library and Archives Service, circulation activities remain manually administered during the transition toward digitalization, creating administrative and operational constraints. This study aimed to examine circulation service management, identify its principal challenges, and assess librarian performance. A descriptive qualitative approach was employed, involving five purposively selected informants: the Head of the Library Division, one circulation service officer, and three library users. Data were collected through interviews, observation, and documentation. Circulation service management was analyzed using George R. Terry’s framework of planning, organizing, actuating, and controlling. The findings indicate that all four management functions have been implemented but remain suboptimal, particularly regarding the dissemination of service plans, staff scheduling, workload distribution, and follow-up on evaluation results. The principal challenges include limited resources, reliance on manual transaction records, and difficulties in locating library collections. Although librarians demonstrate satisfactory interpersonal performance when assisting users, their technical and administrative performance requires improvement. The study concludes that strengthening management practices and accelerating the digitalization of circulation services are essential to improving operational efficiency and service quality. These findings provide practical guidance for library administrators seeking to optimize librarian performance and modernize circulation management in resource-constrained public libraries.